2018
DOI: 10.1007/s11121-018-0895-4
|View full text |Cite
|
Sign up to set email alerts
|

The Protecting Strong African American Families Program: a Randomized Controlled Trial with Rural African American Couples

Abstract: This study presents results from a randomized controlled trial of the Protecting Strong African American Families (ProSAAF) program, a family-centered intervention designed to promote strong couple, coparenting, and parent-child relationships in two-parent African American families. A total of 346 African American couples with an early adolescent child participated; all families lived in rural, low-income communities in the southern USA. Intent-to-treat growth curve analyses involving three waves and spanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(94 citation statements)
references
References 45 publications
(62 reference statements)
6
75
0
Order By: Relevance
“…These versions added work on co‐parenting through support enhancements primarily (e.g., not interfering with the other parent's discipline attempts). The last two programs simultaneously targeted co‐parenting, parent–child, and romantic relationships (Promoting Strong African‐American Families, Barton et al, 2018; Beach et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…These versions added work on co‐parenting through support enhancements primarily (e.g., not interfering with the other parent's discipline attempts). The last two programs simultaneously targeted co‐parenting, parent–child, and romantic relationships (Promoting Strong African‐American Families, Barton et al, 2018; Beach et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Many of these couples will not experience a decline in relationship satisfaction even in the absence of intervention, rendering primary prevention strategies inert and diverting resources away from the subpopulation of couples who will experience relationship distress and perhaps dissolution. Thus secondary prevention—in this case, disseminating interventions specifically to couples who display early indications of risk for distress, whether by virtue of their personal, interpersonal, or environmental vulnerabilities—holds greater potential for promoting healthy marriage (e.g., Barton et al, ; also see Heyman et al, ).…”
Section: Trajectories Of Marital Satisfactionmentioning
confidence: 99%
“…They found short‐term positive impacts on communication quality (between parents) for the intervention group compared with randomized controls, and further demonstrated that these short‐term impacts were associated with less arguing in front of children 2 years after the intervention. In another RCT on an updated version of the program, the team found significant impacts on a variety of measures of relationship quality up through at least 1.5 years after the intervention and that changes in communication associated with the intervention fully mediated these effects (Barton et al, , ).…”
Section: Evidencementioning
confidence: 99%